2020
DOI: 10.1111/deci.12419
|View full text |Cite
|
Sign up to set email alerts
|

Investment Strategies in Supplier Development under Capacity and Demand Uncertainty

Abstract: We study joint investment by a buyer and a supplier in improving the supplier's capacity using a Stackelberg game model. We analyze both buyer‐led and supplier‐led situations. We show that in both cases the players have an opportunistic behavior toward investment. In the buyer‐led game, when the buyer finds the supplier motivated enough to invest, he avoids any direct contribution on capacity improvement. In this situation, the buyer follows an order inflation strategy to increase the investment of the supplie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 88 publications
0
3
0
1
Order By: Relevance
“…In particular, [16] investigated the optimal strategies for firms to invest in their manufacturers, where the benefits of such investments can spill over to other firms who also source from the same manufacturers. In [17], the joint investment by a buyer and a manufacturer in improving the manufacturer's capacity using a Stackelberg game model was studied. The results showed that, although the order inflation strategy increases the buyer's optimal order quantity, it does not co-ordinate the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In particular, [16] investigated the optimal strategies for firms to invest in their manufacturers, where the benefits of such investments can spill over to other firms who also source from the same manufacturers. In [17], the joint investment by a buyer and a manufacturer in improving the manufacturer's capacity using a Stackelberg game model was studied. The results showed that, although the order inflation strategy increases the buyer's optimal order quantity, it does not co-ordinate the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Odak firma ile tedarikçiler arasındaki ilişkilerin geliştirilmesinde uygulanan bilgi paylaşımı ve tedarikçi geliştirme uygulamalarının, aynı zamanda odak işletmenin performansını ve rekabet gücünü artırması beklenir [44]. Günümüzde, işletmelerin müşteri taleplerini yerine getirebilme kabiliyetleri tedarikçilerinin performansına bağımlı hale gelmiştir [45]. Tedarikçilerin geliştirilmesi, fırsatçı davranış riskini ve belirsizlikleri azaltacaktır [44].…”
Section: A Tedari̇k Zi̇nci̇ri̇ Ri̇sk Azaltma Strateji̇leri̇unclassified
“…Nevertheless, each of these practices serves a distinct purpose and does not contribute equally (Routroy and Pradhan, 2014). These practices must be carefully and wisely identified, which is the most to be implemented so that both the manufacturing firms and suppliers can localize the investment for the SD program (Golmohammadi and Hassini, 2021;. The wise selection of practices will ensure that the investment in terms of finances, commitment, and time is worthwhile, especially for firms with limited resources .…”
Section: Introductionmentioning
confidence: 99%